Explicit and Implicit Rights Common to All the Faithful in The Code of Canon Law - Maddineni , Sarath Chandra Sagar (Université Saint-Paul / Saint Paul University, 2018)
This study identifies and analyses the explicit and implicit rights in the Code of Canon Law that are common to all the faithful, that is, the canonical rights of all the baptized christifideles and, in particular, the Catholic faithful. Excluded, therefore, is a consideration of the special rights of particular groups of the faithful such as the laity, clerics, religious, office holders, married persons, etc. Although the focus of the thesis is on the canons of the Latin Code, the counterpart canons of the Code of Canons of the Eastern Churches are always noted when they exist. Explicit rights in canon law are indicated by the word ius or a synonym of same. An implicit right has no explicit terminology indicating a right, but the right is implied in the meaning of the law. Mostly, such rights are implied in the legal obligations of office holders and ministers. That they are obliged by law to do something for the benefit of the faithful implies a concomitant right of the faithful that it be done. Other requirements of the law may also give rise to implicit rights. These can only be known by a careful study and interpretation of the law considered in text and context. There are also certain Latin grammatical expressions commonly used in canon law for obligations or other requirements of law, and frequently these are indicators of an implied right.
Keywords: Rights; Faithful; Implicit Rights; Explicit Rights